School Context and the Effect ESL Placement on Mexican-Origin Adolescents’ Achievement - Callahan, Rebecca (2008)
OBJECTIVES: Immigrant adolescents’ academic achievement is crucial to our future economic stability, and Mexican-origin linguistic minority youth in U.S. schools generally demonstrate lower levels of achievement. English as a Second Language (ESL) programs provide an institutional response to these students’ needs, the effect of which may vary by the proportion of immigrant students in the school. MEASURES: Using propensity score matching and data from the Adolescent Health and Academic Achievement Study (AHAA) and the National Longitudinal Study of Adolescent Health (Add Health), we estimate the effect of ESL placement on Mexican-origin achievement for first-, second-, and third-generation adolescents separately in schools with many and few immigrant students. RESULTS: The estimated effect of ESL placement varies by both immigrant concentration in the school and by students’ generational status. CONCLUSIONS: We find that ESL enrollment may be protective for second-generation Mexican-origin adolescents in high immigrant concentration schools, and may prove detrimental for first-generation adolescents in contexts with few other immigrant students.